2006
DOI: 10.1590/s0034-72992006000200016
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologia dos abscessos peritonsilares

Abstract: Aim: The objective of the present study was to analyze the microbiology of peritonsillar abscesses. Methods: Thirty patients, mean age 24,2 years, with peritonsillar abscesses underwent aspiration of at least 3 mL of pus, which was cultured for aerobes and anaerobes. Results: 87% samples showed positive cultures. Aerobic or facultative aerobic bacteria were isolated from 23% aspirates, mixed aerobic and anaerobic bacteria from 60%, and anaerobic bacteria from only 3% aspirate. A total of 69 bacterial isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Most cases of PTA have a polymicrobial infection 1 . Commonly found organisms include Streptococci, anaerobes and staphylococci.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of PTA have a polymicrobial infection 1 . Commonly found organisms include Streptococci, anaerobes and staphylococci.…”
mentioning
confidence: 99%
“…There are no UK or international guidelines regarding sending PTA aspirates for culture nor as to the antibiotic treatment. It is common practise to start patients empirically on a penicillin prior to culture being obtained 1 . Cheruki reported that by the time culture reports were available, most patients were clinically improved and treatment was not changed 4 …”
mentioning
confidence: 99%
“…A imediata incisão e drenagem é o tratamento de escolha, pois complicações graves decorrentes de abscessos peritonsilares são observados em prontossocorros (SAKAE et al, 2006).…”
Section: A Resposta é C)unclassified